Challenges and Opportunities for Madrasah in Improving The Competence of Graduate Students - Putra, Ali Musri Semjan; Siregar, Kardina Engelina (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to find out what madrasa strategies are in increasing the competence of graduate students in facing the globalization era at MAN 1 Pekanbaru and the factors that influence it. The informants in this study were school principals, curricula deputy heads, teachers and students of MAN 1 Pekanbaru. The madrasa strategy in increasing the competence of graduate students in facing the era of globalization at MAN 1 Pekanbaru is; 1) Changing the curriculum by adding material related to globalization; 2) Increasing the competence of teacher professionalism; 3) Changing the mindset of the teacher; 4) Improving the quality of madrasas; 5) Evaluate learning activities. Based on the results of observations, interviews, and documentation, it was found that the madrasah challenges were; 1) There is globalization; 2) Shifting educational paradigm; 3) Low public trust in madrasah productivity; 4) IT-based learning; 5) Curriculum changes; 6) Competence of madrasah graduates; 7) human resources produced by madrasas; 8) Network and collaboration of madrasah graduates.